Thoracoscopic Sublobectomy for Lung Cancer in a Patient with Unilateral Absence of Pulmonary Artery: Case Report and Narrative Review - Ai, Jiangshan; Zhao, Lianzheng; Gao, Huijiang (Annals of Thoracic and Cardiovascular Surgery, 2024)
Unilateral absence of a pulmonary artery (UAPA) is an uncommon congenital anomaly. Among the rarer conditions, UAPA with lung cancer has been previously reported in 13 cases; however, there remains controversy regarding the surgical approach and precautions. Herein, we present a case study of a 56-year-old female patient who was incidentally diagnosed with a nodule in the right lower lobe of the lung during a routine physical examination and subsequently found to have an absent right pulmonary artery upon preoperative evaluation. A wedge resection of the right lower lobe was performed as treatment. Postoperative pathology confirmed invasive adenocarcinoma (pT1N0M0). We provide a narrative review of existing literature on these patients and discuss optimal surgical management strategies.